Unleashing the Power of Organizational Culture: Impact on Civil Servants' Performance - Fizar Sepriandy; Lubna Salsabila; Timbul Dompak; Etika Khairina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The research aims to explore and understand the key factors that contribute to a positive organizational culture, including leadership style, communication practices, recognition and rewards systems, and opportunities for growth and development. A strong and supportive culture promotes employee engagement, teamwork, innovation, and a sense of belonging, which in turn enhances individual and collective performance. Conversely, a negative or toxic culture can undermine motivation, collaboration, and overall productivity. The research reveals key factors that contribute to a positive organizational culture, including leadership style, communication practices, recognition and rewards systems, and opportunities for growth and development. Recommendations are provided for government agencies and policymakers to foster a healthy and empowering organizational culture that nurtures and motivates civil servants to perform at their best. The findings emphasize the importance of robust institutional frameworks in achieving government effectiveness. A well-functioning legislature, in collaboration with other institutions, is vital for crafting policies that address societal needs and enhance public services. Furthermore, effective governance requires the government to tackle significant challenges in a comprehensive and cooperative manner, engaging both internal and external stakeholders.